Surface characterization of different surface treatments associations with plasma and bonding analysis of Y-TZP and the veneering ceramic - Bitencourt, Sandro Basso [UNESP]; dos Santos, Daniela Micheline [UNESP]; Bastos-Bitencourt, Natália Almeida; Rangel, Elidiane Cipriano [UNESP]; da Cruz, Nilson Cristino [UNESP]; Bonfante, Estevam Augusto; De Souza, Grace Mendonça; Pesqueira, Aldiéris Alves [UNESP] (Elsevier, 2021)
Objectives: To characterize the surface of zirconia (Y-TZP) submitted to different surface treatments (with and without plasma associations) and to evaluate the shear bond strength (SBS) between veneering ceramic (VC) and Y-TZP after different aging methods. Methods: 301 Y-TZP specimens were fabricated and distributed into 7 groups: C (control): no treatment; Al: airborne abrasion with 27 μm Al2O3 particle; L: liner; P: plasma; Al + L: airborne + liner; Al + P: airborne + plasma; P + L: plasma + liner. The Y-TZP surface was characterized by SEM, EDS, AFM, surface profilometry, surface-free energy (SFE), and XRD. SBS between Y-TZP and VC was verified after three aging protocols: initial, after hydrothermal aging (autoclave for 5 h), or thermal fatigue (30,000 baths – 5–55 °C). One- (profilometry, SFE) and two-way ANOVA (SBS), and Tukey's HSD test were used. Results: For the plasma groups, a full globular surface coverage was observed (SEM, AFM). Si was found for Al, L, Al + L, and P + L. Roughness was lower for C, P, and Al + P. For SFE, the highest values were found when the liner was applied (>74.59 nm/Nm). The highest monoclinic content was observed for Al + L (6.96%) and Al + P (5.86%). For the initial period, Al and P + L presented the lowest SBS values (<5.85 MPa; P > 0.331). The highest SBS values were found for L, P, and P + L (hydrothermal aging) and for P, L, Al + L, and Al + P (thermal fatigue). Significance: Changes in Y-TZP topography and the SBS with the VC were found, according to treatments performed. Plasma treatment improved SBS and did not cause phase transformation.
Keywords: Bonding; Plasma; Surface treatment; Veneering ceramic; Zirconia